The Concept of Li'an and Its Legal Basis from the Perspective of Islamic Law - Ade Sultan Muhammad; R. Fahmi Natigor Daulay (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
This study examines the concept of li'an in Islamic law and its legal implications for marriage and the nasab (lineage) status of children. The purpose of this study is to analyze the legal basis, procedures, and legal consequences of li'an from a fiqh perspective, as well as its relevance within the Indonesian legal system. This study employs a normative research method with juridical and theological approaches. The findings indicate that li'an constitutes a legitimate legal mechanism in Islam for resolving accusations of adultery in the absence of witnesses, resulting in the dissolution of marriage and the severance of the child's lineage relationship with the biological father. In the context of Indonesian law, the concept of li'an has not been explicitly regulated in statutory legislation, thus its application faces both juridical and practical constraints. This study concludes that a reconstruction of the li'an concept is necessary in order to align it with the development of modern law and the protection of children's rights.